PENGARUH PROMOSI KESEHATAN DENGAN METODE CERAMAH DAN METODE CERAMAH DENGAN MEDIA VIDEO TERHADAP PERILAKU IBU HAMIL TENTANG PERSALINAN AMAN DI WILAYAH KERJA PUSKESMAS BATUNADUA PADANGSIDEMPUAN TAHUN 2015 - Restu Yuliani; Evawany Y Aritonang; Syarifah Syarifah (Poltekkes Kemenkes Medan, 2017)
Health promotion is basically a process of communication and behavior change process through health education. Health promotion activities can achieve maximum results, if the methods and media health promotion is of great concern and must be adapted to the target. The type of research was a quasi experimental (quasi experimental) with a pretest-posttest design, The population in this study, all pregnant women are entering the third trimester gestational age 37-39 weeks, in the region of 40 health centers Padangsidempuan Batunadua pregnant women. Samples numbered 40 pregnant women are 20 pregnant women group lecture and 20 pregnant women media group lecture with video media. The data were analyzed by using univariat and bivariat analysis with paired sample t-test pairs. The results showed that there are significant health promotion with a lecture and lecture with video media to change knowledge and attitudes of pregnant women on safe childbirth and health promotion methods most influential in improving knowledge, attitudes and actions of pregnant women in conducting safe childbirth in the work area Padangsidempuan Batunadua health centers is a lecture with video media. Need to improve knowledge and attitudes about safe childbirth so as to provide encouragement and support to pregnant women who give birth safely, health workers Batunadua Health Center suggested to use a lecture with video media in delivering health promotion to pregnant mothers because of a lecture with video media can portray a moving object together with natural sounds or sound accordingly.